2022
DOI: 10.1111/scd.12772
|View full text |Cite
|
Sign up to set email alerts
|

A case of giant dental calculus in a patient with centronuclear myopathy

Abstract: Introduction Centronuclear myopathy is a hereditary congenital muscle disease. It is characterized by generalized muscle hypotonia from early childhood, elongated cacial appearance, mandibular undergroth, and dental malposition. In this report, we discuss the clinical course and management of a patient with centronuclearmyopathy, who developed a giant dental calculus in the floor of the mouth and underwent surgical excision. Case Report A 37‐year‐old Japanese man was referred to our hospital, and reported a sw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…2 ). Abnormally high amounts of calculus deposition could occasionally be seen in modern patients, but the underlying cause is unidentifiable in most cases 55 , 56 . At least, this individual would not have a routine tooth cleaning habit during the period of calculus deposition.…”
Section: Discussionmentioning
confidence: 99%
“…2 ). Abnormally high amounts of calculus deposition could occasionally be seen in modern patients, but the underlying cause is unidentifiable in most cases 55 , 56 . At least, this individual would not have a routine tooth cleaning habit during the period of calculus deposition.…”
Section: Discussionmentioning
confidence: 99%
“…Stable isotope analysis showed that HM2-HA-3 had a similar diet to other individuals from the Hamanaka 2 site and other individuals from Hamanaka 2 site displayed little or no calculus deposition (Figure 2). Abnormally high amounts of calculus deposition could occasionally be seen in modern patients, but the underlying cause is unidentifiable in most cases 68,69 . At least, this individual would not have a routine tooth cleaning habit during the period of calculus deposition.…”
Section: Discussionmentioning
confidence: 99%